Iron coupling with carbon fiber to stimulate biofilms formation in aerobic biological film systems for improved decentralized wastewater treatment: Performance, mechanisms and implications. (January 2021) - Feng, Qian; Guo, Wen; Wang, Tong; Cristina Macias Alvarez, Laura; Luo, Miaomiao; Ge, Ran; Zhou, Changren; Zhang, Qin; Luo, Jingyang
Graphical abstract: Highlights: The pollutants removal were improved and accelerated in ICF, especially for PO4 3− . ICF altered the surface properties of carriers to stimulate the biofilms formation. The amounts and components of biomass in biofilms were significantly increased. The abundances of functional microorganisms were evidently enriched in ICF. The microbial activities ( i.e. metabolic enzymes and genes) were highly expressed. Abstract: Iron coupling with carbon fiber (ICF) as carriers to stimulate the biofilms formation for decentralized wastewater treatment was proposed. The typical pollutants removal was accelerated and enhanced (increased by 13.65% for chemical oxygen demand, 19.68% for ammonia nitrogen and 32.66% for phosphate) in ICF compared with the traditional carbon fiber (CF) system. Mechanism explorations indicated that the iron coupling improved the surface properties of carbon fibers and contributed to the attachment and growth of biomass significantly. The components of biomass were changed with increasing proteins proportion in ICF, which was beneficial to the biofilms formation and stability. The microbial community was altered with the enrichment of functional microorganisms ( i.e. Pseudomonas and Thauera ). Moreover, the microbial metabolic functions ( i.e. enzymatic activities and encoding genes) involved in pollutants removal derived from decentralized wastewater were highly expressed in ICF. This work provided an effective strategy to enhance the decentralized wastewater treatment.